3 Decades of force measurement on vault in gymnastics - Knoll, Kl.; Naundorf, F.; Bronst, A.; Wagner, R.; Brehmer, S.; Lehmann, T. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Force measurement on gymnastics apparatuses can give useful knowledge about technique of gymnasts, but also on injury prevention and stress on the human body. Since 1986 direct force measurements on vault horse and tables were applied by our researchers. Aim of this paper is to publish information about the technology we used for direct force measurements. All measuring systems were customized to the apparatuses from different manufacturers. Most measures were arranged in training sessions, but we report also about data collection in official competitions. Examples of force patterns give an idea of peak forces and impulse during different vault groups (handspring, Kasamatsu).